Membangun Konsep Diri Positif Melalui Peer Group Sebagai Manajemen Diri Dampak Bullying Pada Remaja Putri - Prafitri, Lia Dwi; Budiarto, Eka; Suparni, Suparni; Zuhana, Nina (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2025)
Young women in orphanages often experience psychosocial challenges, such as low self-esteem and experiences of bullying, which affect their emotional and social well-being. This service aims to improve self-concept through a peer group approach as a self-management strategy against the impact of bullying. The methods used include focused group discussions (FGD), education, peer group formation, role play, mentoring, and evaluation. The results show an increase in self-concept understanding, the formation of an active and supportive peer group, improvement in self-management skills, increased self-confidence, the development of peer group modules or guides, and the establishment of sustainable partnerships. Pre-test to post-test scores increased by an average of 1.4 points. Peer groups are effective in creating a safe environment and strengthening positive interactions between adolescents. This intervention has a positive impact on the psychosocial aspect and has the potential to be replicated in other orphanages as a form of promotive and preventive mental health. Cross-sectoral support, such as caregivers, educators, and health workers, is needed for sustainable programs and optimal results.Keywords: bullying; self-concept; orphanage; peer group; young women  Abstrak: Remaja putri di panti asuhan sering mengalami tantangan psikososial, seperti rendahnya konsep diri dan pengalaman bullying, yang memengaruhi kesejahteraan emosional dan sosial mereka. Pengabdian ini bertujuan meningkatkan konsep diri melalui pendekatan peer group sebagai strategi manajemen diri terhadap dampak bullying. Metode yang digunakan meliputi diskusi kelompok terfokus (FGD), edukasi, pembentukan kelompok sebaya, role play, pendampingan, dan evaluasi. Hasil capaian menunjukkan peningkatan pemahaman konsep diri, terbentuknya peer group yang aktif dan suportif, peningkatan kemampuan manajemen diri, peningkatan rasa percaya diri, tersusunnya modul atau panduan peer group dan terjalinnya kemitraan berkelanjutan. Skor pre-test ke post-test naik rata-rata 1,4 poin. Peer group terbukti efektif menciptakan lingkungan aman dan memperkuat interaksi positif antarremaja. Intervensi ini memberikan dampak positif pada aspek psikososial dan berpotensi direplikasi di panti lain sebagai bentuk promotif dan preventif kesehatan mental. Dukungan lintas sektor seperti pengasuh, pendidik, dan tenaga kesehatan diperlukan agar program berkelanjutan dan hasilnya optimal.Kata kunci: bullying; konsep diri; panti asuhan; peer group; remaja putri